Gold nanoparticles stabilized by sulfonated-imidazolium salts as promising catalyst in water - Monti, Gustavo Antonio (2019)
We present the total characterization (by FT-IR and NMR spectroscopies) of gold nanoparticles (Au-NPs) stabilized by different sulfonated-imidazolium salts. Also, thermogravimetric analysis (TGA) was used in order to evaluate the degree of the Au-NPs coverage. Our results show how the orientation of the sulfonated-imidazolium salts and, the interaction of the hydrocarbon chain with the Au-NP surface are responsible for the strength of the ligand-Au-NP interaction. The developed procedure is easy, fast and reproducible to carry out different catalytic organic reactions in water. Our preliminary studies indicate that Au-NPs synthesized are active and recyclable catalysts for the reduction of aromatic nitro compounds at room temperature in water.